Nonlinearity and sex differences in the performance of a polygenic risk score for juvenile idiopathic arthritis - Haftorn, Kristine Løkås; Rudsari, Hamid Khoshfekr; Jaholkowski, Piotr Pawel; Dåstøl, Vilde Øverlien; Hestetun, Sigrid Valen; Andreassen, Ole A.; Weinberg, Clarice R.; Sanner, Helga (Frontiers in Immunology, 2025)
BackgroundJuvenile idiopathic arthritis (JIA) is an immune-mediated pediatric disease believed to result from a complex interplay of genetic and environmental factors. Genome-wide association studies have enabled calculation of polygenic risk scores (PRS) for JIA. Understanding how the PRS associates with JIA and whether it performs similarly across sexes is essential for its utility in future studies.MethodsWe studied the relationship between a PRS developed from a previously published genome-wide association study of JIA and JIA in children from the Norwegian Mother, Father and Child Cohort Study (MoBa; total n = 57,630; JIA cases = 238). Generalized linear models (GLM) and generalized additive models (GAM) were used in logistic regression to assess the association. Furthermore, we investigated whether the relationship between PRS and JIA differed by sex by applying GAM models with interaction terms.ResultsPRS was significantly associated with JIA using both GLM (p< 2e-16) and GAM (p< 2e-16) models, and our results indicated a nonlinear relationship between PRS and JIA (effective degrees of freedom, EDF = 1.96). We found a significant interaction between sex and JIA PRS in relation to JIA (p = 0.017), and indications of a stronger and more logit-nonlinear relationship in females (EDF = 1.82) versus males (EDF = 1.06).ConclusionThe relationship between PRS and JIA was slightly logit-nonlinear for females and logit-linear for males. The PRS for JIA can likely be used either as a continuous or discrete variable in analyses, but sex-stratification is recommended for future studies.